2011
DOI: 10.1586/erd.10.62
|View full text |Cite
|
Sign up to set email alerts
|

Combination of noninvasive brain stimulation with pharmacotherapy

Abstract: Noninvasive brain stimulation (NIBS) techniques are being increasingly investigated as a therapeutic approach for neuropsychiatric disorders. One method is to combine NIBS with pharmacotherapy to enhance the clinical effects or avoid an increase in drug dosages to decrease the incidence of side effects. However, few studies to date have investigated the relative and combined efficacy of NIBS with pharmacotherapy. Based on a literature review of previous studies and meta-analyses for major depression, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…40,41 With these data, we estimated a 3-point difference effect (effect size of Cohen d=0.5) for both tDCS only and sertraline only vs placebo and a combined additive effect in the combined treatment group (ie, 6-point difference, with an effect size of Cohen d=1.0), which, considering probabilities of 5% for type I error and 20% for type II error, resulted in an estimated sample size of 30 patients per arm for a total of 120 participants (for an extensive discussion regarding our power analysis, see the articles by Brunoni et al 29,42 ). Further, we considered a difference smaller than an effect size of 0.5 or a 3-point between-group difference not to be clinically relevant per the National Institute for Clinical Excellence guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 With these data, we estimated a 3-point difference effect (effect size of Cohen d=0.5) for both tDCS only and sertraline only vs placebo and a combined additive effect in the combined treatment group (ie, 6-point difference, with an effect size of Cohen d=1.0), which, considering probabilities of 5% for type I error and 20% for type II error, resulted in an estimated sample size of 30 patients per arm for a total of 120 participants (for an extensive discussion regarding our power analysis, see the articles by Brunoni et al 29,42 ). Further, we considered a difference smaller than an effect size of 0.5 or a 3-point between-group difference not to be clinically relevant per the National Institute for Clinical Excellence guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…One important issue is the association of tDCS with pharmacotherapy. Pharmacological studies have shown that drugs can not only enhance but also abolish tDCS effects (Brunoni et al, 2011g;Stagg and Nitsche, 2011). Although this evidence comes from preliminary, single-session tDCS studies that stimulated the motor cortex (not the PFC) of healthy volunteers, it is important to investigate whether and which drug therapies could modify tDCS effects, specially considering that patients with MDD commonly use a plethora of medicines of different classes, such as antidepressants, anti-epileptics, antipsychotics, lithium and benzodiazepines.…”
Section: Tdcs and Pharmacotherapymentioning
confidence: 99%
“…It also seems to have additional advantages when compared with transcranial magnetic stimulation (TMS): in particular, tDCS is relatively more portable, affordable, tolerable and, perhaps, also safer Zaghi et al , 2009 ;Brunoni et al , 2011a ). Furthermore, tDCS can be combined with pharmacotherapy to enhance its clinical effects and/or reduce adverse effects by avoiding drug dosage increases (Brunoni et al , 2011c ).…”
Section: Introductionmentioning
confidence: 99%